HERBS CLASSIFICATION WITH USAGE IDENTIFICATION USING DEEP LEARNING TECHNIQUES. - SUJATHA, R.; ARTHI, K.; PRATHIBA, S.; PRIYANKA, R. A.; SATHIYA, P. (Turkish Journal of Physiotherapy Rehabilitation, 2021)
The aim of instinctive plant image is to find the hopeful solution for traversing the botanical typology gap, which has gotten a lot of attention from anatomy and software scientists alike. As machine learning technology improves, more advanced prototypes for automated plant identification software have been proposed. Since medicinal plants have less side effects and are less expensive than modern medicine, they are gaining popularity in the pharmaceutical industry. There are a number of ways to improve the classifier's ability to correctly identify herbal medicines in real time. The use of various efficient and accurate machine learning algorithms for plant classifications using leaf images in recent years is reviewed in this paper. For certain machine learning classifiers, the analysis includes image processing methods for detecting leaves and extracting essential leaf features. These deep learning classifiers are classified based on their success when analysing leaf icon using traditional plant features such as shape, vein, texture, and a combination of multiple features that are evaluated using the company's own database. Then, with an enhanced accuracy rate, retrieve the results regarding diseased leaf consumption.